OʻQUVCHILARNING IJODIY FAOLIYATI MALAKALARINI SHAKLLANTIRISHNING SAMARADORLIK KOʻRSATKICHLARI - Reymov, Q.D.; Artikov, M.B.; Aytoreev, A.I.; Bazarbayeva, L.G. (SCIENCE and SOCIETY, 2025)
The article presents improved indicators of the methodology for developing students’ creative activity skills in chemistry education. The process of forming is illuminated the methodological views of a chemistry teacher and their implementation in practice.
Keywords: students; statistical analysis; knowledge level; qualification; research effectiveness; empirical value; critical value; methodological system; goal; content; form; method; means of control